Improving Students Aesthetic Culture Through Art Therapy Using "Shashmakom" Melodies - Turayevich, Yarashev Jurabek (International Journal on Integrated Education, 2026)
The article examines the pedagogical and therapeutic possibilities of using the Mushkulot section of the unique example of the national musical heritage "Shashmaqom" in improving the aesthetic culture of students. In particular, based on art therapy methods, a technology is developed that allows revealing the aesthetic and expressive potential of the Mushkulot melodies and effectively organizing the educational process on this basis. Additionally, the paper introduces a specialized teaching technology developed for integrating the Mushkulot melodies into the educational process. This technology focuses on revealing the aesthetic and expressive potential of the music, while ensuring that students engage with the melodies in a way that nurtures both their artistic and emotional growth. The article highlights how this technology supports an interdisciplinary approach, combining pedagogy with therapeutic art practices, and offers a framework for educators to effectively organize and implement lessons that promote a more profound understanding of music as an emotional and cultural expression. Through this approach, students are encouraged not only to appreciate the aesthetic qualities of Shashmaqom but also to explore its therapeutic potential, contributing to their personal development and overall well-being.